2021
DOI: 10.1073/pnas.2012208118
|View full text |Cite
|
Sign up to set email alerts
|

Global citation inequality is on the rise

Abstract: Citations are important building blocks for status and success in science. We used a linked dataset of more than 4 million authors and 26 million scientific papers to quantify trends in cumulative citation inequality and concentration at the author level. Our analysis, which spans 15 y and 118 scientific disciplines, suggests that a small stratum of elite scientists accrues increasing citation shares and that citation inequality is on the rise across the natural sciences, medical sciences, and agricultural sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 52 publications
3
72
0
1
Order By: Relevance
“…This issue is self-perpetuating due to reliance on citation metrics, which reflect deeply entrenched biases and exclusionary networks that disadvantage systemically marginalized groups, and these citation metric biases continue to rise globally [20].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is self-perpetuating due to reliance on citation metrics, which reflect deeply entrenched biases and exclusionary networks that disadvantage systemically marginalized groups, and these citation metric biases continue to rise globally [20].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
“…While there have been recent successes in increasing diversity among trainees and early-career researchers [ 8 , 9 ], differential recruitment, retention, and promotion rates with respect to age, sex, gender, race, and ethnicity continue to perpetuate the lack of diversity among all career levels of scientists [ 14 , 17 19 ]. This issue is self-perpetuating due to reliance on citation metrics, which reflect deeply entrenched biases and exclusionary networks that disadvantage systemically marginalized groups, and these citation metric biases continue to rise globally [ 20 ].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Sciencementioning
confidence: 99%
“…This index is based on the author's publication records and the number of citations, balancing the importance of low-cited or non-cited articles while imputing more weight to highly cited articles. The extensive use of citation metrics as indicator of scientifi c productivity, however, has been recently challenged due to the potential to perpetuate disadvantages of minoritized groups favoring citation elites (Nielsen and Andersen 2021 ). Although our current scientifi c reward system in science is based on quantity of publications and citations, which perpetuates sexist and racist "rewards" through narrowly prioritizing citations and impact factors, it has been suggested that we should shift our value system to broadly include metrics of justice, equity, diversity, and inclusion (Davies et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This index is based on the author's publication records and the number of citations, balancing the importance of low-cited or non-cited articles while imputing more weight to highly cited articles. The extensive use of citation metrics as indicator of scientific productivity, however, has been recently challenged due to the potential to perpetuate disadvantages of minoritized groups favoring citation elites (Nielsen and Andersen 2021). Although our current scientific reward system in science is based on quantity of publications and citations, which perpetuates sexist and racist "rewards" through narrowly prioritizing citations and impact factors, it has been suggested that we should shift our value system to broadly include metrics of justice, equity, diversity, and inclusion (Davies et al 2021).…”
Section: Discussionmentioning
confidence: 99%